Comparative Genome Microsynteny Illuminates the Fast Evolution of Nuclear Mitochondrial Segments (NUMTs) in Mammals - Uvizl, Marek; Puechmaille, Sebastien J; Power, Sarahjane; Pippel, Martin; Carthy, Samuel; Haerty, Wilfried; Myers, Eugene W; Teeling, Emma C; Huang, Zixia (Molecular biology and evolution, 2024)
The escape of DNA from mitochondria into the nuclear genome (nuclear mitochondrial DNA, NUMT) is an ongoing process. Although pervasively observed in eukaryotic genomes, their evolutionary trajectories in a mammal-wide context are poorly understood. The main challenge lies in the orthology assignment of NUMTs across species due to their fast evolution and chromosomal rearrangements over the past 200 million years. To address this issue, we systematically investigated the characteristics of NUMT insertions in 45 mammalian genomes and established a novel, synteny-based method to accurately predict orthologous NUMTs and ascertain their evolution across mammals. With a series of comparative analyses across taxa, we revealed that NUMTs may originate from nonrandom regions in mtDNA, are likely found in transposon-rich and intergenic regions, and unlikely code for functional proteins. Using our synteny-based approach, we leveraged 630 pairwise comparisons of genome-wide microsynteny and predicted the NUMT orthology relationships across 36 mammals. With the phylogenetic patterns of NUMT presence-and-absence across taxa, we constructed the ancestral state of NUMTs given the mammal tree using a coalescent method. We found support on the ancestral node of Fereuungulata within Laurasiatheria, whose subordinal relationships are still controversial. This study broadens our knowledge on NUMT insertion and evolution in mammalian genomes and highlights the merit of NUMTs as alternative genetic markers in phylogenetic inference.
Keywords: Mitochondria; savci; molekulární evoluce; Cell Nucleus; Phylogeny; genom mitochondriální; mitochondriální DNA; Sequence Analysis, DNA; Evolution, Molecular; mammal; Genome, Mitochondrial; DNA, Mitochondrial; genomika; buněčné jádro; mitochondrie; zvířata; Mammals; sekvenční analýza DNA; fylogeneze; genome microsynteny; Animals; Genomics; evolution; nuclear mitochondrial DNA segment (NUMT)